2015
DOI: 10.1111/mec.13251
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome structure of the fungid coral Ctenactis echinata aligns with environmental differences

Abstract: The significance of bacteria for eukaryotic functioning is increasingly recognized. Coral reef ecosystems critically rely on the relationship between coral hosts and their intracellular photosynthetic dinoflagellates, but the role of the associated bacteria remains largely theoretical. Here, we set out to relate coral‐associated bacterial communities of the fungid host species Ctenactis echinata to environmental settings (geographic location, substrate cover, summer/winter, nutrient and suspended matter concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 49 publications
3
113
3
Order By: Relevance
“…Indeed, here we found pronounced differences in the coral bacterial microbiome of in situ and ex situ E. fistula. Changes in the microbial community based on environmental differences were shown before by Roder et al (2015) where the microbiome of Ctenactis echinata was less structured and more diverse in lower populated coral habitats, indicating that preferred habitats align with more structured bacterial communities. A more extreme case of environmental adjustment was observed by Röthig et al (2016) where associated bacteria of Fungia granulosa changed under high salinity exposure over 29 days and suggested a shift toward increased osmolyte production, sulfur oxidation, and nitrogen fixation.…”
Section: Microbiome Differences In E Fistula Between Native Red Sea mentioning
confidence: 90%
See 3 more Smart Citations
“…Indeed, here we found pronounced differences in the coral bacterial microbiome of in situ and ex situ E. fistula. Changes in the microbial community based on environmental differences were shown before by Roder et al (2015) where the microbiome of Ctenactis echinata was less structured and more diverse in lower populated coral habitats, indicating that preferred habitats align with more structured bacterial communities. A more extreme case of environmental adjustment was observed by Röthig et al (2016) where associated bacteria of Fungia granulosa changed under high salinity exposure over 29 days and suggested a shift toward increased osmolyte production, sulfur oxidation, and nitrogen fixation.…”
Section: Microbiome Differences In E Fistula Between Native Red Sea mentioning
confidence: 90%
“…In particular, adjustment of associated bacteria to prevailing environmental conditions has been suggested to support acclimatization of the coral holobiont (Reshef et al, 2006). This notion is supported by recent studies that show, at least in part, flexible bacterial microbiomes of the coral holobiont to environmental change (Jessen et al, 2013;Roder et al, 2015;Hernandez-Agreda et al, 2016;Röthig et al, 2016;Ziegler et al, 2016Ziegler et al, , 2017. However, our knowledge on the role of the bacterial microbiome to coral holobiont function is still limited (Bourne and Webster, 2013;Bourne et al, 2016), although bacteria are shown to contribute to coral health (Rosenberg et al, 2007;Krediet et al, 2013) and are involved in nutrient cycling (Rädecker et al, 2015;Bourne et al, 2016).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…studies (e.g., Littman et al, 2009;Pantos et al, 2015;Roder et al, 2015) have suggested that geographic location and environmental settings can determine the holobiont microbiome, whereas others (e.g., Hentschel et al, 2002;Fraune and Bosch, 2007;Montalvo and Hill, 2011;Lawler et al, 2016) have shown that bacterial communities are species-specific associations conserved over time and space. Moreover, coevolution of bacteria and coral has been proposed (Thompson et al, 2015), as it was demonstrated for Endozoicomonas symbionts in corals with contrasting life-history traits and across global scales (Bayer et al, 2013;Neave et al, 2016Neave et al, , 2017.…”
Section: Exaiptasia H2 and Cc7 Strains Only Share A Small Common Micrmentioning
confidence: 99%